One‐year metreleptin improves insulin secretion in patients with diabetes linked to genetic lipodystrophic syndromes. Issue 7 (12th January 2016) - Vatier, C.; Fetita, S.; Boudou, P.; Tchankou, C.; Deville, L.; Riveline, JP.; Young, J.; Mathivon, L.; Travert, F.; Morin, D.; Cahen, J.; Lascols, O.; et al.
Abstract : Recombinant methionyl human leptin (metreleptin) therapy was shown to improve hyperglycaemia, dyslipidaemia and insulin sensitivity in patients with lipodystrophic syndromes, but its effects on insulin secretion remain controversial. We used dynamic intravenous (i.v.) clamp procedures to measure insulin secretion, adjusted to insulin sensitivity, at baseline and after 1 year of metreleptin therapy, in 16 consecutive patients with lipodystrophy, diabetes and leptin deficiency. Patients, with a mean [± standard error of the mean (s.e.m.)] age of 39.2 (±4) years, presented with familial partial lipodystrophy (n = 11, 10 women) or congenital generalized lipodystrophy (n = 5, four women). Their mean (± s.e.m.) BMI (23.9 ± 0.7 kg/m 2 ), glycated haemoglobin levels (8.5 ± 0.4%) and serum triglycerides levels (4.6 ± 0.9 mmol/l) significantly decreased within 1 month of metreleptin therapy, then remained stable. Insulin sensitivity (from hyperglycaemic or euglycaemic‐hyperinsulinaemic clamps, n = 4 and n = 12, respectively), insulin secretion during graded glucose infusion (n = 12), and acute insulin response to i.v. glucose adjusted to insulin sensitivity (disposition index, n = 12), significantly increased after 1 year of metreleptin therapy. The increase in disposition index was related to a decrease in percentage of total and trunk body fat. Metreleptin therapy improves not only insulin sensitivity, but also insulin secretion in patients with diabetes attributable to genetic lipodystrophies.